Impact of training and development towards employee performance at Yayasan Melaka / Amirah Najwa Hashim - Hashim, Amirah Najwa (Faculty of Business and Management, 2018)
The issue of this research is at Yayasan Melaka, number of training provided to their staffs has been reduced. This is because the financial resources that implemented a series of training programed were going down since 2016. The results of this research are based on these three objectives. First is to determine the types of training programme that can influence the performance of staff at Yayasan Melaka. Second is to study the correlation between training and development and employees’ performance at Yayasan Melaka. Lastly is to examine whether training can influence the performance of staff at Yayasan Melaka. The methodology for this research are first frequency was used for type of training. Next correlation analysis was used to achieves the second objective and last multiple regression analysis was used to test the hypothesis. Data was gathered by distribute questionnaire to employees at Yayasan Melaka. Then, the data are analysed using SPSS (Statistical Package for the Social Science) version 20.0. The findings of this research are first, seminars get the highest score type of training that can influence the performance of the staffs at Yayasan Melaka. Second finding is training and development is significantly positively correlated to employee performance. Lastly, the finding shows training and development has positive relationship with employee performance.